Anti-Arthritic and Anti-Inflammatory Constituents from Medicinal Plants - Murugananthan G., Sudheer Kumar G., Sathya Chethan P., and Mohan S (Journal of Applied Pharmaceutical Science, 2013)
Inflammatory arthritis is a common problem observed in elderly people. Nearly one fifth of the world population suffers from this debilitating disease. Traditional medicines like Siddha, Ayurveda, Unani and Chinese medicines have mentioned few herbal drug remedies for arthritis but lack in providing scientific evidence of therapeutic benefits. However, past few decades showed great achievements in the herbal drug standardization due to the development in modern chromatographic techniques. Numbers of plants are studied extensively for their traditional claim with respect to the chemical constituents and extraction techniques. These anti-inflammatory drugs are commercialized as herbal medicines after standardizing the extracts from natural sources. In this article, we made an attempt to summarize the medicinal plants screened for arthritis with respect to the chemical constituents and therapeutic moieties.
Keywords: Arthritis, Inflammatory, Herbs, Extracts, Constituen